Motivations and Tactics of Militant Islamist Movements - Ibraheem , Nawar (International Journal of Psychosocial Rehabilitation, 2020)
Radical Islamist terrorism is defined as any terrorist act, set of acts, or campaign committed by groups or individuals who profess Islamist motivations or goals. Islamism is a concept whose meaning has been debated in both public and academic contexts. The term can refer to movements that call for the full implementation of sharia. It is commonly used interchangeably with the terms political Islam or Islamic fundamentalism. In Western media, usage of the term tends to refer to groups who aim to establish a sharia-basedIslamicstate, often with the implication of violent tactics and human rights violations, and has acquired connotations of political extremism. This term used to describe an Islamic political or social activist. Coined in preference to the more common term “Islamic fundamentalist.” Most belong to Islamic organizations or social movements. Islamismtakes different forms and spans a wide range of strategies and tactics towards the powers in place—"destruction, opposition, collaboration, indifference" that have varied as circumstances have changed, and thus is not a united movement.